Stress as a Risk Factor for Substance Use Disorders: A Mini-Review of Molecular Mediators - Mukhara, Deepika; Banks, Matthew L.; Neigh, Gretchen N. (Frontiers in Behavioral Neuroscience, 2018)
A collective review of the existing literature demonstrates that stress can increase susceptibility to drug addiction. Despite a strong correlation between stress and susceptibility, a developed picture of the mechanisms by which stress impacts cocaine dependence via the mesolimbic pathway are not fully defined. In this mini-review, we highlight three mechanisms by which glucocorticoids and the dopaminergic system interact. In light of this interplay, we examine recent literature on cocaine dependence at critical points in the mesolimbic pathway including the ventral tegmental area (VTA) and nucleus accumbens (NAcs). Furthermore, we clarify the role of stress in cocaine dependence at these important points. Taken together, the available literature suggests that stress augments the influence of cocaine addiction at multiple points along the VTA mesolimbic projection and uniquely in the NAcs through a positive feedback mechanism. Further research is required to outline the interaction between the prefrontal cortex (PFC) and key molecular mediators including ΔFosB, CREB, and CDK5 which are highlighted in this mini-review. Ultimately, a more complete understanding of the biological interactions between the circuitry which mediates addiction, and that which responds to stressor exposure, will facilitate the identification of novel prevention and treatment strategies.